Native Seattle : Histories from the Crossing-Over Place - Thrush, Coll-Peter, 1970- (Book collections on Project MUSE., 2017)
This updated edition of Native Seattle brings the indigenous story to the present day and puts the movement of recognizing Seattle's Native past into a broader context. Native Seattle focuses on the experiences of local indigenous communities on whose land Seattle grew, accounts of Native migrants to the city and the development of a multi-tribal urban community, as well as the role Native Americans have played in the narrative of Seattle.